Chaos management in organizations: factors that influence the transition from uncertainty of balance within the educational community - Orellana Guevara, Catty (2025)
This essay shows the need to respond to the conditions faced by the people who make up an educational community to find balance in the face of the constant emergencies that arise today and alter the structure of their identity. When the institutional condition is rigid and inflexible, it must be mobilized to avoid falling behind in this era of globalization. The problem lies in the lack of theory regarding management in the administration of education to address chaos. The essay uses the methodology of descriptive research to expose and discuss the factors that intervene when groups face changes that alter the functioning of their organizational structure, unleash chaos and, in turn, generate reactions in group interaction that affect the work of education, among them: uncertainty, imbalance, self-organization and order. Therefore, the objective of this dissertation is to place management in the main states that people in the community are educational. Thus, it is concluded that management focused on each moment of the dynamics of a group that seeks its balance is an opportunity to stabilize and revitalize the function of education.